Pulsed vector atomic magnetometer using an alternating fast-rotating field - Tao Wang; Wonjae Lee; Mark Limes; Thomas Kornack; Elizabeth Foley; Michael Romalis (Nature Communications)
Abstract We introduce a vector atomic magnetometer that employs a fast-rotating magnetic field applied to a pulsed 87Rb scalar atomic magnetometer. This approach enables simultaneous measurements of the total magnetic field and its two polar angles relative to the rotation plane. Operating in gradiometer mode, the magnetometer achieves a total field gradient sensitivity of 35 $${{{\rm{fT}}}}/\sqrt{{{{\rm{Hz}}}}}$$ fT / Hz (0.7 parts per billion) and angular resolutions of 6 $${{{\rm{nrad}}}}/\sqrt{{{{\rm{Hz}}}}}$$ nrad / Hz at a 50 μT Earth field strength. The noise spectra remain flat down to 1 Hz and 0.1 Hz, respectively. Here we show that this method overcomes several metrological challenges commonly faced by vector magnetometers and gradiometers. We propose a unique peak-altering modulation technique to mitigate systematic effects, including a newly identified dynamic heading error. Additionally, we establish the fundamental sensitivity limits of the sensor, demonstrating that its vector sensitivity approaches scalar sensitivity while preserving the inherent accuracy and calibration benefits of scalar sensors. This high-dynamic-range, ultrahigh-resolution magnetometer offers exceptional versatility for diverse applications.